A agricultura familiar camponesa e a reestruturação produtiva no agronegócio da avicultura de corte industrial no estado da Paraíba - Buriti, Maria Marta dos Santos (2022)
Guided by the capitalist principle of multiplication of the gains through the conjunction of agriculture, industry and market, productive restructuring has advanced in the Brazilian field as a movement of transformation and contradiction: on one hand, it is driven by the (capitalist) effort of forging a dynamic stage of uninterrupted growth, on the other hand, it is pressured by the increasingly unsolvable limits of the capital development at present. As for Paraíba, productive restructuring has created a scenario of socio-productive and territorial changes with striking effects over the broiler industry, reorganized under forms of accumulation more flexible and with incentives to the increase of the return of capital. Strongly supported by the State, such activity was initially stimulated by the need to reassure the rupture with rudimentary production bases, typical in the mid-1970s, and enter a new and competitive technical, financial, marketing level given the increasing competition in Brazilian poultry industry. With such diligence, the confluence of public and private investments soon enabled the consolidation of the poultry agribusiness and its expansion as of the 1990s through the integration system, which started articulating, in the production scale of broilers, poultry enterprises and rural producers coming from both industrial and peasant family farming. Given such scenario, productive restructuring began to be put in place in the field through processes much more complex than the simplistic conjecture of homogenization assumed by the market logic, since the non-capitalist relations appear as mediators of the determinations prescribed by the capital throughout its restructuring. Based on such statement, the purpose of this study was to understand the productive restructuring in the broiler industry in the state of Paraíba and its impact on the field from the contradictory relationship of interdependence between the capital production of agribusiness and the social production in peasant family farming. Under the analytical principles of dialectic, we set up a methodological path organized from a qualitative approach supported by a structured bibliographical research, based on a theoretical-conceptual plan articulated by the concepts of space, territory, peasant family farming and productive restructuring, as well as discussions related to the characterization of the poultry agribusiness; and a field research in a region comprising six municipalities (Pocinhos, Boa Vista, Soledade, Olivedos, Montadas and Puxinanã), delimited according to variables that converge with the core purpose of the study. The reflections made during this study enabled elaborating the thesis that the collection of social demands from the integrated peasant farmer and the economic-productive demands from the poultry agribusiness endorses a relationship of interdependence between both. Although denied and compelled by the subordination bonds imposed by the integrating companies, not only does it legitimate the peasant production conditions, but it can subsidize the organization of forms of resistance by the integrated peasants facing the exploratory relationship conducted by the capital in the agribusiness.